2017
DOI: 10.1021/acs.jpclett.7b00945
|View full text |Cite|
|
Sign up to set email alerts
|

Spectral Response of Plasmonic Gold Nanoparticles to Capacitive Charging: Morphology Effects

Abstract: We report a study of the shape-dependent spectral response of the gold nanoparticle surface plasmon resonance at various electron densities to provide mechanistic insight into the role of capacitive charging, a topic of some debate. We demonstrate a morphology-dependent spectral response for gold nanoparticles due to capacitive charging using single-particle spectroscopy in an inert electrochemical environment. A decrease in plasmon energy and increase in spectral width for gold nanospheres and nanorods was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 65 publications
7
82
0
Order By: Relevance
“… 28 – 34 For instance, existing studies have shown that the LSPR band of AuNRs immobilized on the ITO substrate is subject to a blue-shift when applying a negative potential, which is due to the increase in the electron density of AuNRs under the electrochemical charging. 35 38 We accordingly recorded the corresponding scattering spectrum of a single AuNR at different potentials as shown in Fig. 1a .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 – 34 For instance, existing studies have shown that the LSPR band of AuNRs immobilized on the ITO substrate is subject to a blue-shift when applying a negative potential, which is due to the increase in the electron density of AuNRs under the electrochemical charging. 35 38 We accordingly recorded the corresponding scattering spectrum of a single AuNR at different potentials as shown in Fig. 1a .…”
Section: Resultsmentioning
confidence: 99%
“…The results are nicely consistent with literature reports. 35 , 37 , 38 To date, maximal scattering wavelength ( λ max ) is the major optical parameter that reflects the electron density of AuNRs. Because it usually takes several seconds or even longer time to acquire a scattering spectrum, it is impossible to determine the λ max when applying an alternating potential as high as tens of kilohertz.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmonic responses can be easily observed in dark-field imaging. Therefore, combining electrochemical measurements with dark-field microscopy [96][97][98], particularly hyperspectral dark-field imaging is valuable [99]. The charge carrier density can be precisely controlled by altering the applied potential and allowing for real-time optical monitoring of the affected LSP resonance responses [97,98,100].…”
Section: Plasmonic Photocatalytic Electrochemical Measurementsmentioning
confidence: 99%
“…Therefore, combining electrochemical measurements with dark-field microscopy [96][97][98], particularly hyperspectral dark-field imaging is valuable [99]. The charge carrier density can be precisely controlled by altering the applied potential and allowing for real-time optical monitoring of the affected LSP resonance responses [97,98,100]. Using hyperspectral dark-field imaging, Byers et al [99] demonstrated that upon electrochemical tuning, a population of nanoparticles can undergo several processes ranging from nanoparticle charging to electrochemical reactions, such as chloride ion oxidation and hydrogen evolution reaction.…”
Section: Plasmonic Photocatalytic Electrochemical Measurementsmentioning
confidence: 99%
“…The spectral changes due to applied electrochemical potentials have mainly but not always 49 been attributed to two effects occurring inside the particles rather than in the surrounding electrolyte: 50 The first is capacitive charging, which alters the electron density in the metal and thus the effective plasma frequency. 47,51 The second is specific ion adsorption, which creates a lossy optical surface layer.…”
Section: Direct Electrochemical Controlmentioning
confidence: 99%